2002
DOI: 10.1093/jhered/93.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Narrow Leaflet Gene for Yield and Agronomic Traits in Soybean

Abstract: Genes that affect plant form and function may be used to enhance the yield of soybean [Glycine max (L.) Merr.]. Most soybean cultivars have broad (ovate) leaflets. A single gene, ln, controls inheritance for the narrow leaflet characteristic. Narrow leaflet cultivars (ln/ln) also tend to have a higher percentage of four-seeded pods than ovate (Ln/Ln) leaflet cultivars. Heterozygous (Ln/ln) plants have a leaflet shape intermediate between narrow and ovate. Determining the agronomic effects of the narrow leaflet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
4
24
2
1
Order By: Relevance
“…Differences in leaflet shape and pod type between Ln and ln soybean plants have been repeatedly assessed in different soybean (Takahashi, 1934;Domingo, 1945;Weiss, 1970;Bernard and Weiss, 1973;Mandl and Buss, 1981;You et al, 1995;Dinkins et al, 2002;Jeong et al, 2011). These studies have consistently shown that Ln plants tend to have broader leaflet shapes (Figures 2A and 2B) and lower NSPP than ln plants ( Figures 2C and 2D).…”
Section: The Ln Phenotype and Its Expressionmentioning
confidence: 85%
See 1 more Smart Citation
“…Differences in leaflet shape and pod type between Ln and ln soybean plants have been repeatedly assessed in different soybean (Takahashi, 1934;Domingo, 1945;Weiss, 1970;Bernard and Weiss, 1973;Mandl and Buss, 1981;You et al, 1995;Dinkins et al, 2002;Jeong et al, 2011). These studies have consistently shown that Ln plants tend to have broader leaflet shapes (Figures 2A and 2B) and lower NSPP than ln plants ( Figures 2C and 2D).…”
Section: The Ln Phenotype and Its Expressionmentioning
confidence: 85%
“…Previous agronomic studies on the ln locus using isogenic lines (Mandl and Buss, 1981), diverse cultivars (You et al, 1995), and broad (Ln/Ln), heterozygous (Ln/ln), and narrow (ln/ln) leaflet types (Dinkins et al, 2002) have repeatedly found that broad and narrow leaflet soybean genotypes have similar seed yields, but narrow leaflet plants consistently produce smaller seeds than those of broad leaflet plants. The fact that the narrow leaflet plants tend to produce a greater number of seeds has garnered a great deal of attention, particularly in the development of soybean cultivars for sprouts.…”
Section: Introductionmentioning
confidence: 99%
“…Bernard and Weiss assigned a new gene symbol, ln, to the narrow leaflet trait. Similarly, Dinkins et al (2002) reported that leaflet types were genotypically marked as follows: narrow leaflet (ln/ln), intermediate leaflet (Ln/ln), and ovate leaflet (Ln/Ln).…”
Section: A B Cmentioning
confidence: 97%
“…In Japan, Sawada (1988) who studied the crossing result between broad leaflet soybean and narrow one, found that the value of LSI < 2.6 was constantly used to classify the broad leaflet while the value of LSI > 2.6 was used to classify the narrow leaflet. Porter et al (2000) classified the leaf shape into ovate and narrow leaflet, but Dinkins et al (2002) used different classification of the leaf shape, which is used in this study i.e. narrow, intermediate, and ovate leaflet.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation